Standarisasi Jumlah Armada Trucking Haulage Berdasarkan Jumlah Bongkar Muat pada PT. X - Patricia Angelina Dewi; I Gede Agus Widyadana (Jurnal Titra, 2022)
In loading and unloading container activities at the terminal, a trucking fleet will be needed. PT. X is a company that engaged in domestic and international logistics shipping. The company’s current problem is that there are containers that stacked in the terminal stacking yard. Some factors that can this problem is due to the imbalance of loading and unloading activities with the trucking haulage assignment. The percentage of the company containers stacked in the terminal stack yard reaches 6,9 percent and they desires to accomplish unloading activity in less than five hours. The company wants to determine the standard of the truck fleets so that the need for trucks is not less and not more, so it will be well drafted. This research uses simulation method with Promodel software to model the system. The simulation results of the initial model shows that there are 36 boxes stacked from the request for unloading 500 boxes using 30 trucks to move them. The results of the proposed simulation show that using 39 trucks to move 500 boxes does not result in containers stacked in the terminal stacking yard and achieves the company desire to accomplish the unloading activity within five hours.